QARAQALPAQ ÁDEBIYATÍNDA WATAN MOTIVINIŃ KÓRKEM TALQÍLANÍWÍ (ART AND CULTURE BULLETIN, 2026)
This article highlights the role and artistic significance of the motif of the Motherland in Karakalpak literature. The historical destiny, national identity, and spiritual values of the Karakalpak people are analyzed in close connection with the concept of the Motherland. Using the works of Berdaq and Ajiniyoz as examples, the article reveals ideas of love for the Motherland, concern for the fate of the homeland, and the education of the people in the spirit of unity and patriotism. In addition, the relevance of the motif of the Motherland in modern Karakalpak literature and its  educational significance are discussed.
Keywords: Motherland; Karakalpak literature; patriotism; national identity; Berdaq’s works; Ajiniyoz’s works; people’s destiny; spiritual values; modern literature.